Accuracy of preoperative clinical staging for locally advanced gastric cancer in KLASS-02 randomized clinical trial - Kim, Dong Jin; Hyung, Woo Jin; Park, Young-Kyu; Lee, Hyuk-Joon; An, Ji Yeong; Kim, Hyoung-Il; Kim, Hyung-Ho; Ryu, Seung Wan; Hur, Hoon; Kim, Min-Chan; Kong, Seong-Ho; Kim, Jin-Jo; et al. (Frontiers in Surgery, 2022)
Purpose: The discrepancy between preoperative and final pathological staging has been a long-standing challenge for the application of clinical trials or appropriate treatment options. This study aimed to demonstrate the accuracy of preoperative staging of locally advanced gastric cancer using data from a large-scale randomized clinical trial. Materials and Methods: Of the 1050 patients enrolled in the clinical trial, 26 were excluded due to withdrawal of consent (n=20) or non-surgery (n=6). The clinical and pathological staging was compared. Risk factor analysis for underestimation was performed using univariate and multivariate analyses. Results: Regarding T staging by computed tomography, accuracy rates were 74.48, 61.62, 58.56, and 85.16% for T1, T2, T3 and T4a, respectively. Multivariate analysis for underestimation of T staging revealed that younger age, ulcerative gross type, circular location, larger tumor size, and undifferentiated histology were independent risk factors. Regarding nodal status estimation, 54.9% of patients with clinical N0 disease were pathologic N0, and 36.4% of patients were revealed to have pathologic N0 among clinical node-positive patients. The percentage of metastasis involvement at the D1, D1+, and D2 lymph node stations significantly increased with the advanced clinical N stage. Among all patients, 29 (2.8%), including 26 with peritoneal seeding, exhibited distant metastases. Conclusions: Estimating the exact pathologic staging remains challenging. A thorough evaluation is mandatory before treatment selection or trial enrollment. Moreover, we need to set a sufficient case number when we design the clinical trial considering the stage migration.